2020
DOI: 10.5194/acp-20-7801-2020
|View full text |Cite
|
Sign up to set email alerts
|

Radiative forcing of anthropogenic aerosols on cirrus clouds using a hybrid ice nucleation scheme

Abstract: Abstract. Anthropogenic aerosols impact cirrus clouds through ice nucleation, thereby changing the Earth's radiation budget. However, the magnitude and sign of anthropogenic forcing in cirrus clouds is still very uncertain depending on the treatments for ice-nucleating particles (INPs), the treatments for haze particle freezing, and the ice nucleation scheme. In this study, a new ice nucleation scheme (hereafter the HYBRID scheme) is developed to combine the best features of two previous ice nucleation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 76 publications
1
20
1
Order By: Relevance
“…In the present study we therefore focus on both the microphysical and the dynamic aspects, by analysing the uncertainties related to the assumptions on aviation soot INP characteristics and exploring the impact of different (simplified) representations of the dynamic forcing in the model. We stress again that the main goal of this study is (Möhler et al, 2005;Koehler et al, 2009;Crawford et al, 2011;Kanji et al, 2011;Chou et al, 2013;Kulkarni et al, 2016;Mahrt et al, 2018;Nichman et al, 2019;Mahrt et al, 2020) compared with the values assumed in model studies on the impact of aviation soot on cirrus (Hendricks et al, 2005;Penner et al, 2009;Liu et al, 2009;Hendricks et al, 2011;Gettelman and Chen, 2013;Zhou and Penner, 2014;Penner et al, 2018;Zhu and Penner, 2020). The parameters explored in this study are symbolized with stars.…”
Section: Uncertainties In the Soot-cirrus Effectmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present study we therefore focus on both the microphysical and the dynamic aspects, by analysing the uncertainties related to the assumptions on aviation soot INP characteristics and exploring the impact of different (simplified) representations of the dynamic forcing in the model. We stress again that the main goal of this study is (Möhler et al, 2005;Koehler et al, 2009;Crawford et al, 2011;Kanji et al, 2011;Chou et al, 2013;Kulkarni et al, 2016;Mahrt et al, 2018;Nichman et al, 2019;Mahrt et al, 2020) compared with the values assumed in model studies on the impact of aviation soot on cirrus (Hendricks et al, 2005;Penner et al, 2009;Liu et al, 2009;Hendricks et al, 2011;Gettelman and Chen, 2013;Zhou and Penner, 2014;Penner et al, 2018;Zhu and Penner, 2020). The parameters explored in this study are symbolized with stars.…”
Section: Uncertainties In the Soot-cirrus Effectmentioning
confidence: 93%
“…Using the same model with the Kärcher et al (2006) parametrization for ice nucleation and an improved scheme for subgrid-scale vertical updrafts, Penner et al (2018) simulated an aircraft effect on cirrus clouds of −200 mW m −2 , considering S crit = 1.35 and again f act = 0.6% as a result of soot pre-processing in contrails. A subsequent study, using the CESM model featuring a hybrid ice nucleation scheme combining the best features of the Liu and Penner (2005) and Kärcher et al (2006) parametrizations, updated this estimate to −140 mW m −2 , assuming a slightly lower S crit = 1.2 (Zhu and Penner, 2020). In the most recent work on this subject, McGraw et al (2020) used the CESM2 model with the cirrus nucleation scheme by Barahona and Nenes (2009) and found that aicraft soot can perturb cirrus clouds in the Norther Hemisphere, with effects both in the shortwave and in the longwave radiative forcing, but they were not able to extract a statistically significant signal from their model simulations.…”
mentioning
confidence: 99%
“…We acknowledge that more recent estimates on aviation emissions and associated inventories have been published since. However, we estimate that uncertainties in model estimates for a given year are still larger than differences between individual years; hence, using the year 2006 provides us with more consistency when comparing our results with studies of individual effects [14,[21][22][23] that also use 2006 inventories. Additionally, the scientific understanding of the effects of nitrogen oxides has progressed recently, requiring our results to be put in the context of the methodology applied and the question investigated.…”
Section: Discussionmentioning
confidence: 63%
“…Future studies are needed to identify the most realistic case for quantifying the altitude dependence of the aerosol effect in more detail. We stress again that these studies focus on the modifications of warm liquid clouds and do not consider the radiative effects of possible modifications of natural cirrus clouds due to soot particles from aviation, e.g., [22,43,44]. In view of the large persisting uncertainties in the current quantifications of this effect, we leave the integration of this process to future aviation-climate assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation